2011
DOI: 10.1002/elan.201100351
|View full text |Cite
|
Sign up to set email alerts
|

Sol‐Gel Derived Nanostructured Metal Oxide Platform for Bacterial Detection

Abstract: O1 gene based 24-mer single stranded deoxyribonucleic acid probe (ssDNA) has been immobilized onto sol-gel derived nanostructured zirconium oxide (NanoZrO 2 ) film fabricated onto indium-tin-oxide (ITO) coated glass plate to detect Vibrio cholerae. The X-ray diffraction and Atomic Force Microscopy techniques have been used to characterize the nanostructured ZrO 2 (particle size of~30-40 nm) and the ssDNA/ZrO 2 bioelectrode. The hybridization of ssDNA/ZrO 2 bioelectrode with the complementary and genomic DNA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…An analytical device for cholera detection based on antibody-conjugated ZrO 2 NPs has recently been reported 29 . In another study, an electrochemcial gold electrode modified with polytryamine was found to be sensitive at attomolar concentrations of cholera 30 .…”
Section: Discussionmentioning
confidence: 99%
“…An analytical device for cholera detection based on antibody-conjugated ZrO 2 NPs has recently been reported 29 . In another study, an electrochemcial gold electrode modified with polytryamine was found to be sensitive at attomolar concentrations of cholera 30 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Carbon allotropes, like graphene oxide (GO), fullerenes, carbon nanotubes, etc., have been explored for cellular imaging, tissue engineering, intercalation materials, drug delivery biomaterials and biosensors. [7][8][9][10][11] For biosensor fabrication, the presence of available functional groups (e.g. hydroxyl, epoxide, carbonyl, carboxyl, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This represents a healthy research activity with a 16% growth rate annually [ 79 ]. Biosensors should offer quick and efficient detection of viral diseases with high levels of specificity and sensitivity [ 80 ]. These criteria are crucial in the success or failure of the detection technology.…”
Section: How Are Biosensors and Bioelectronics Beneficial For Virus Dmentioning
confidence: 99%